Impact of Green Investment and Jobs on Poverty via Sustainable Development - Yendra Kardiansya; Ketut Sukiyono; Izharudin Izharudin (UNIVED Press, Dehasen University Bengkulu, 2024)
Purpose: This study evaluates the influence of green investment and green jobs on poverty reduction with sustainable development as a mediating variable. Methodology: Using a descriptive-quantitative method, secondary data from the Central Bureau of Statistics of South Sumatra from 2016-2020 were analyzed using a panel regression model. Results: The results indicate that green investment and green jobs affect poverty reduction through sustainable development in South Sumatra Province. Findings: Challenges include green infrastructure development and policies supporting green investment and job creation. Novelty: This research provides insights into the impact of green investment and green jobs on poverty reduction within the context of sustainable development. Originality: The study offers a detailed analysis of how green investment and green jobs contribute to poverty reduction and sustainable development. Conclusions: Green investment and green jobs have the potential to reduce poverty and achieve sustainable development but require collaboration among the government, private sector, and society. Type of Paper: Empirical Research Article